The ENT run through pilot: a questionnaire survey of 23 trainees. Issue 1 (22nd January 2021) - Heward, E; Kumar, B N
Abstract: Objective: The ENT run through pilot was introduced in 2018 to improve early recruitment to the specialty. This study aimed to understand what makes a successful interview applicant and the experience of the run through trainees during the specialty trainee one and specialty trainee two years. Method: A questionnaire survey was sent to all ENT run through trainees. Results: Twenty-three trainees responded. Of the successful candidates, 74 per cent held additional degrees prior to application. The median core surgical interview rank was 27 (range: 3–174). Trainees felt that being on the run through pilot had increased ENT trainer engagement. Conclusion: The ENT run through posts are highly competitive, and holding an additional degree may improve applicant success. The pilot programme has been successful by increasing trainer engagement at this critical stage of training. These results will enable development of the pilot programme and provide valuable information for those applying to an ENT run through post.